Teaching Recognition Platform Auxiliary Teaching Convenience - et. al., Y. M. Fei , (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
How to make good use of the network technology, to help teachers understand students’ e-portfolios quickly, and thus to adjust the teaching method. Teachers can use various teaching methods to help students’ learning effectiveness is one valuable key in today’s technical education development. One or Two weeks of registration period after school start. Most teachers cannot quickly know student's portfolio on paper in the first couple of weeks in Taiwan. And student's portfolio on paper cannot show their learning results in this course. As a result, it leads to a no effectiveness teaching work. The goal of the study is to use Facial Expression Detection Technology with Network Cloud Service (Teaching Recognition Platform, TRP) pass students’ e-portfolios to teacher. Teacher’s teaching method can fit into the students’ need in class. This study, teacher is to wear a pair glasses with a miniature camera and a Bluetooth teacher uses the camera to get the pictures of students’ faces and sending them by Bluetooth. The Bluetooth then passes a signal on telling the wireless network to connect the images to the schools’ learning database. By using it, the teacher can rapidly get their students’ e-portfolios back in time from the schools’ learning database by all the available mobile such as laptop, PDA, PAD, Smart Phone, etc. By the TRP, teachers can adjust teaching contents and methods and make their teaching more pleasant and effective.